The Mystery of Grave 16 - Blečić Kavur, Martina (No Limits, 2023)
The hilly region of eastern Slovenia, with its wide river valleys and narrow tributaries, was the area where the cemeteries of the Urnfield culture such as Ruše and Pobrežje were discovered. They have shaped our understanding of the material culture and chronology of the Late Bronze Age. Since their discovery, the cemeteries in eastern Slovenia have been included in major discussions about the cultural characteristics of the phenomenon that encompassed large parts of Europe at the end of the second millennium BCE. A phenomenon that, due to the almost universal burial rite and nearly total absence of wealthy burials, triggered numerous assumptions about the society structure and the religious foundations of observable practices. Perhaps most fascinating was the discovery of grave 16, the resting place of a high-status woman.